IDEAL-D Framework for Device Innovation: A Consensus Statement on the Preclinical Stage. Issue 1 (January 2022) - Marcus, Hani J.; Bennett, Amy; Chari, Aswin; Day, Toni; Hirst, Allison; Hughes-Hallett, Archie; Kolias, Angelos; Kwasnicki, Richard M.; Martin, Janet; Rovers, Maroeska; Squire, Sarah E.; McCulloch, Peter
Abstract : Objective: To extend the IDEAL framework for device innovation, IDEAL-D, to include the preclinical stage of development (stage 0). Background: In previous work, the IDEAL collaboration has proposed frameworks for new surgical techniques and complex therapeutic technologies, the central tenet being that development and evaluation can and should proceed together in an ordered and logical manner that balances innovation and safety. Methods: Following agreement at the IDEAL Collaboration Council, a multidisciplinary working group was formed comprising 12 representatives from healthcare, academia, industry, and a patient advocate. The group conducted a series of discussions following the principles used in the development of the original IDEAL framework. Importantly, IDEAL aims for maximal transparency, optimal validity in the evaluation of primary effects, and minimization of potential risk to patients or others. The proposals were subjected to further review and editing by members of the IDEAL Council before a final consensus version was adopted. Results: In considering which studies are required before a first-in-human study, we have: (1) classified devices according to what they do and the risks they carry, (2) classified studies according to what they show about the device, and (3) made recommendations based on the principle that the more invasive and high risk a device is, the greater proof required of their safety and effectiveness before progression to clinical studies (stage 1). Conclusions: The proposed recommendations for preclinical evaluation of medical devices represent a proportionate and pragmatic approach that balances the de-risking of first-in-human translational studies against the benefits of rapid translation of new devices into clinical practice.